Implementasi Metode Design Sprint Dalam Pengembangan Situs Web Pencari Kerja - Octafian, D Tri; Yudistira, Pilde; Kurniawan, M Agil; Paturrahman, Arif; Priyadi, Rahmat; Setiawan, Eko (Universitas Multi Data Palembang, 2024)
The market’s needs in software development are an important point to be fulfilled by developers; if not, the developed software cannot contribute much to users, and as a result, the developed software will be left by its users. The goal of this research is to implement the Design Sprint method to produce job search software that is suitable to the market’s needs using the Minimum Viable Product (MVP) concept. The Design Sprint method has produced a product MVP to solve job searches based on user domicile. Based on the MVP that was produced, the prototype has been validated by the market with a result of 74.77%, indicating that respondents agree that the job search web JobsIDN has been suitable for their needs. The number of respondents is 111.